Analysis of Precision and Stability of Hand Tracking with Leap Motion Sensor - Vysocký, Aleš; Grushko, Stefan; Oščádal, Petr; Kot, Tomáš; Babjak, Ján; Jánoš, Rudolf; Sukop, Marek; Bobovský, Zdenko (Sensors (Basel, Switzerland), 2020)
In this analysis, we present results from measurements performed to determine the stability of a hand tracking system and the accuracy of the detected palm and finger's position. Measurements were performed for the evaluation of the sensor for an application in an industrial robot-assisted assembly scenario. Human-robot interaction is a relevant topic in collaborative robotics. Intuitive and straightforward control tools for robot navigation and program flow control are essential for effective utilisation in production scenarios without unnecessary slowdowns caused by the operator. For the hand tracking and gesture-based control, it is necessary to know the sensor's accuracy. For gesture recognition with a moving target, the sensor must provide stable tracking results. This paper evaluates the sensor's real-world performance by measuring the localisation deviations of the hand being tracked as it moves in the workspace.
Keywords: hand tracking; biosenzitivní techniky; Gestures; lidé; gesture; Robotics; Hand; collaborative robot; Biosensing Techniques; ruka; gesta; Forecasting; Humans; pohyb těles; Motion; leap motion; robotika; předpověď; robot